Water awareness and bioethical perspectives among medical students at Mersin University Faculty of Medicine: an analytical cross-sectional study comparing academic-stage groups - Selda Okuyaz; Oya Ögenler (Frontiers in Medicine, 2026)
Background The escalating environmental crisis underscores water as a vital bioethical responsibility and public health determinant. Accordingly, water consumption, sustainability, and related ethical responsibilities are relevant topics in medical education. Objective This study aimed to compare water-consumption behaviours, awareness, knowledge, and attitudes toward water use and water-related ethics between Year 3 and Year 6 medical students. Methods This analytical cross-sectional study was conducted at Mersin University Faculty of Medicine, Türkiye, and compared two independent cohorts of medical students (Year 3 and Year 6) to evaluate their knowledge and attitudes toward water consumption from a bioethical perspective. The findings therefore represent cross-sectional associations between academic stage and the measured outcomes in two independent cohorts. Data were collected using a self-administered questionnaire incorporating the Water Consumption Behaviour Scale. Descriptive statistics, chi-square tests, and independent-samples t-tests were used for the analyses. Results A total of 246 medical students participated in the study. Correct-response rates were higher among Year 6 students than Year 3 students for recommended daily water intake (26.3% vs. 7.4%, p < 0.001) and water-conservation practices (61.4% vs. 44.4%, p = 0.025). No significant gender differences were observed in knowledge levels. Water Consumption Behaviour Scale scores differed by academic stage: Year 6 students had higher Water Awareness and Personal and Social Responsibility scores, whereas Year 3 students had higher Water Consumption, Water Pollution, Water Management, and total scores ( p ≤ 0.004). Conclusion Academic stage was associated with distinct patterns of water-related knowledge and scale scores. Year 6 students had higher correct-response rates for two knowledge items, whereas Year 3 students had a higher total Water Consumption Behaviour Scale score. These findings represent cross-sectional associations between academic stage and the measured outcomes in two independent cohorts. The observed patterns identify water ethics, planetary health, and sustainability as relevant topics for medical curricula.